Italian Ornithological Commission (COI) - Report 30 (Avocetta, 2022)
Italian Ornithological Commission (COI) - Report 30. This report refers to records from January 1st 2020 to December 31st 2021, with the addition of a number of records from previous years that were submitted more recently. For each species, the records are listed by date and information is given as follows: English and scientific name, number of accepted records pre- and post-1950 (the numbers in this abstract refer to the total number of records), number of individuals if more than one, age or plumage and sex if known, location, date, names of the observers, and available documentation (photograph, sound recording, specimen, etc.). The taxonomy is in line with the new CISO-COI Italian Checklist, which also includes subspecies and follows the taxonomy adopted by the HBW-BirdLife Check-list, as decided by the CISO council in 2018. A total of 52 records involving 31 taxa were assessed. The following 40 records, involving 23 taxa, were accepted, including eight first records for Italy (Cat. AERC: A – COI Category 1A, 1B): Oriental Turtle-dove Streptopelia orientalis (Friuli- Venezia Giulia 2021, 4th record); Little Swift Apus affinis (Emilia-Romagna 2020, 7th record); White-rumped Swift Apus caffer (Calabria 2020, 1st record and 1st breeding); Allen’s Gallinule Porphyrio alleni (Tuscany 2013, 9th record; Piedmont 2021, 10th record); Atlantic Yellow-nosed Albatross Thalassarche chlororhynchos (Latium 2021, 1st record); Brown Booby Sula leucogaster (Tuscany 2020, 8th record; Liguria 2020, 9th record; Tuscany 2021, 10th record); Pacific Golden Plover Pluvialis fulva (Campania 2020, 17th record; Basilicata 2020, 18th record; Apulia 2020, 19th record); Grey-headed Lapwing Vanellus cinereus (Umbria 2021, 1st record); Whitetailed Lapwing Vanellus leucurus (Apulia 2020, 6th record); Upland Sandpiper Bartramia longicauda (Campania 2013, 11th record); Western Sandpiper Calidris mauri (Lombardy 2021, 1st record); Long-billed Dowitcher Limnodromus scolopaceus (Veneto 2013, 8th record; Latium 2020, 9th record); Lesser Yellowlegs Tringa flavipes (Latium 2021, 12th record; Apulia 2021 13th record); Black-winged Pratincole Glareola nordmanni (Lombardy 2021, 12th record); ‘Russian Mew Gull’ Larus canus heinei (Lombardy 2019-2021, 2nd to 11th records; Emilia-Romagna 2021, 12th record); Heuglin’s Gull Larus fuscus heuglini (Abruzzo 2017, 4th record); Thick-billed Murre Uria lomvia (Liguria 2021, 1st record); Steppe Grey Shrike Lanius excubitor pallidirostris (Apulia 2020, 8th record); Redtailed Shrike Lanius phoenicuroides (Sicily 2021, 1st record); Booted Warbler Iduna caligata (Tuscany 2021, 2nd record); Siberian Trush Geokikla sibirica (Lombardy 2020, 4th record); Black-throated Wheatear Oenanthe seebohmi (Abruzzo 2020, 1st record); Caspian Stonechat Saxicola torquatus hemprichii (Sicily 2019, 5th record). The addition of White-rumped Swift, Atlantic Yellow-nosed Albatross, Grey-headed Lapwing, Western Sandpiper, Thick-billed Murre, Red-tailed Shrike and Black-throated Wheatear brings the Italian list to 557 accepted species. Records not accepted (COI List 5A, 5B) were: Black-browed Albatross Thalassarche melanophris (Tuscany 2021); Yellow-billed Egret Ardea brachyrhyncha (Piedmont 2020); Steppe Whimbrel Numenius phaeopus alboaxillaris (Veneto 2020); Eastern Orphean Warbler Sylvia crassirostris (two records: Friuli-Venezia Giulia 2009-2011; Latium 2019); Ehrenberg’s Redstart Phoenicurus phoenicurus samamisicus (Tuscany 2020); Naumann’s Trush Turdus naumanni (Lombardy 2007); Western Yellow Wagtail Motacilla flava iberiae (Tuscany 2020); Yellow-breasted Bunting Emberiza aureola (Veneto 2019).